1992
DOI: 10.1002/jsfa.2740580413
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive composition of broth from selected bean varieties cooked for various periods

Abstract: Ten bean varieties with white, yellow, red and black seed coats were subjected to cooking regimes of 60, 90 and 120 min on a hot plate. The cooking broth was analysed for total soluble solids, dry matter, protein, tannin, calcium, magnesium, iron and available L-tyrosine during in-vitro protein digestion. The results indicated that tannin levels were high in cooking broth from bean varieties with red seed coats compared with broth from those with white and yellow seed coats. Digestibility was higher in white a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 11 publications
3
23
2
Order By: Relevance
“…It should be stressed that, compared with the raw material, cooked and sterilised bean seeds respectively contained 9-11% and 24-26% less dry matter, depending on the cultivar. Decreases in dry matter content were due to the swelling of starch and absorption of water and also to the leaching of soluble constituents to the medium, particularly in the case of seeds with a high surface to weight ratio (Habiba, 2002;Lisiewska et al, 2007;Lyimo, Mugula, & Elias, 1992). As in the present work, the amino acid loss in sterilised seeds of grass pea was greater than in seeds cooked after freezing, the degree of loss depending on the cultivar .…”
Section: Amino Acid Seedscontrasting
confidence: 52%
“…It should be stressed that, compared with the raw material, cooked and sterilised bean seeds respectively contained 9-11% and 24-26% less dry matter, depending on the cultivar. Decreases in dry matter content were due to the swelling of starch and absorption of water and also to the leaching of soluble constituents to the medium, particularly in the case of seeds with a high surface to weight ratio (Habiba, 2002;Lisiewska et al, 2007;Lyimo, Mugula, & Elias, 1992). As in the present work, the amino acid loss in sterilised seeds of grass pea was greater than in seeds cooked after freezing, the degree of loss depending on the cultivar .…”
Section: Amino Acid Seedscontrasting
confidence: 52%
“…Naoman et al (1988) reported that cooking signi"cantly reduced the content of ash, phosphorus, iron, calcium, and magnesium in the broad bean. However, as in the present study, in their investigation on beans Lyimo et al (1992) and Augustin et al (1981) observed that iron was fairly resistant to leaching. Cooked frozen broad beans contained statistically more phosphorus than canned seeds, while the latter contained signi"cantly more calcium and zinc, except for those produced from Comprimo RS.…”
Section: Lsd For Interaction (I;ii) Lsd For Cultivars (I) Lsd For Scontrasting
confidence: 35%
“…According to Lopez and Williams (1988), El-Shahy et al (1979), Lyimo et al (1992), Maskova et al (1996), Mc Carthy et al (1977, and Sche!eldt et al (1982), during the technological treatments with the use of water the leaching mineral components depend among other factors on the content of these components in the water, the time of treatment, and the surface/weight ratio in seeds. The freezing of broad bean seeds and their storage caused very small and statistically non-signi"cant changes in the level of the constituents analysed (Tables 2}10). After 6-month storage the preparation of frozen seeds for consumption (cooking to consumption consistency) caused a signi"cant decrease in the level of ash, potassium, and zinc and in the cultivars Threefoldwhite and Green Hangdown a signi"cant Mean from four samples, each analysed in duplicate.…”
Section: Resultsmentioning
confidence: 96%
“…Brazil is the first world producer of the species Phaseolus vulgaris [2]. Bean grains contain 20-35% protein and 50-60% carbohydrates, but present antinutritional factors such galactooligosaccharides (GO), mainly raffinose, stachyose and verbascose [3]. The GO are heat resistant and remain in the end product [4].…”
Section: Introductionmentioning
confidence: 99%